Struktura organizacyjna szpitala - stan i perspektywy - Kacała, Joanna (Organizational structure of hospital - states and perspectives, 2006)
This article represents diagnosis organization of hospital. The introduced proposals of changes in structure of organizational unit concern the change of tasks and way of thinking the management and improvement of organizational efficiency of whole hospital
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 564-569